Organic Semiconductors: Carrier‐Selective Traps: A New Approach for Fabricating Circuit Elements with Ambipolar Organic Semiconductors (Adv. Electron. Mater. 3/2017). (March 2017) - Ford, Michael J.; Labram, John G.; Wang, Ming; Wang, Hengbin; Nguyen, Thuc‐Quyen; Bazan, Guillermo C.
Abstract : In article number 1600537, M. J. Ford et al. show that ambipolar polymer semiconductors can be solution processed with molecular additives to control their charge transport properties. The addititives act as carrier‐selective traps, and the researchers show that selecting materials with the appropriate energy level offset can result in either n‐ or p‐type transport from a single ambipolar polymer. Using this discovery, the fabricate efficient complementary inverters with high gain.